2014
DOI: 10.1101/cshperspect.a013623
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cutaneous Squamous Carcinoma Development in the Mouse

Abstract: Cutaneous squamous cell carcinoma (SCC) is one of the most common cancers in Caucasian populations and is associated with a significant risk of morbidity and mortality. The classic mouse model for studying SCC involves two-stage chemical carcinogenesis, which has been instrumental in the evolution of the concept of multistage carcinogenesis, as widely applied to both human and mouse cancers. Much is now known about the sequence of biological and genetic events that occur in this skin carcinogenesis model and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 154 publications
(151 reference statements)
0
24
0
1
Order By: Relevance
“…In this study, we compared tumor series with different fates through analysis of a DMBA-TPA carcinogenesis protocol. Although the DMBA-TPA protocol is limited to the analysis of the tumors initiated by RAS family mutation, it is widely accepted that the mutation landscape, mutation burden, and gene expression profile of the SCCs formed on the mouse back skin through the DMBA-TPA protocol are largely similar to human SCCs such as head and neck, esophageal, lung, and cervical SCCs 14 , 17 , 18 , 36 , 37 . In line with these previous studies, our results indicated that although the carcinogenesis protocol using DMBA-TPA provides information on the initial driver mutations and promotes the formation of a number of papillomas on the mouse skin, further drivers are clearly required for the malignant alteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we compared tumor series with different fates through analysis of a DMBA-TPA carcinogenesis protocol. Although the DMBA-TPA protocol is limited to the analysis of the tumors initiated by RAS family mutation, it is widely accepted that the mutation landscape, mutation burden, and gene expression profile of the SCCs formed on the mouse back skin through the DMBA-TPA protocol are largely similar to human SCCs such as head and neck, esophageal, lung, and cervical SCCs 14 , 17 , 18 , 36 , 37 . In line with these previous studies, our results indicated that although the carcinogenesis protocol using DMBA-TPA provides information on the initial driver mutations and promotes the formation of a number of papillomas on the mouse skin, further drivers are clearly required for the malignant alteration.…”
Section: Discussionmentioning
confidence: 99%
“…SCC is one of the most common cancers in Caucasian populations, and the prognosis of metastatic SCC is extremely poor 14 . The DMBA-induced SCC model is one of the most commonly used in vivo models and is widely used for studying the mechanisms of metastasis 15 , which can be applied to both human and mouse cancers 14 , 16 . High-throughput genome sequencing analysis has previously been conducted for DMBA-induced mouse skin SCCs 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Using this cohort, we induced skin tumors using the chemical carcinogen 7,12-Dimethylbenz(a)anthracene (DMBA) and the tumor promoting agent 12-O-Tetradecanoylphorbol-13-acetate (TPA) [ 7 ]. This protocol initially results in the formation of benign papillomas, a fraction of which will progress into carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the RAS–MAPK pathway is essential for benign tumours and SCCs 7 . Downstream of RAS G12V –MAPK is SOX2, an essential transcription factor induced by SCC-initiating (stem) cells 811 .…”
mentioning
confidence: 99%